Program Pelatihan Bahasa Inggris Dan Kewirausahaan Bagi Pemuda dalam Mendukung Tercapainya Pembangunan Berkelanjutan Di Kecataman Sinjai Timur - J, Jusniaty; B, Baharuddin; Juniati, Sri Rahayu (Idea Pengabdian Masyarakat, 2022)
The community empowerment is one of the support in developing of potential sources of Regional Original Income (PAD). For that, human resources as the pads of confirmation pads need to be powered. One of the elements of human resources is the youth. So one of the potential development efforts is the English training program for Sinjai Timur’s Youth and Entrepreneurship. Types of activities and technical implementation in this program consist of: (1) Pre-Test (Test will be given by the tutor the to target partner before giving the material ), (2) Giving Material (Giving material by Tutor to Target Partners), (3) Post-Test (Test will be given at the end of the training, to know the level of change before and after the training), (4) Brainstorming (covered the idea of entrepreneurship). Based on the results of the implementation of the activity, it was found that the target group’s mastery of English was still less visible from the pre-test to post-test data from the number of existing targets, did not experience significant percentage increases. There were no targets that were able to achieve 100% percentage. For business administration management, only 1 (one) business group can assist in issuing a business license.